Improved Performance of Raft Foundation Using Detached Pile Columns in Loose Subsoil Conditions - Fekadu Melese (Advances in Civil Engineering)
Piles act as settlement reducers in case of connected piled-raft foundation and hence decrease the settlements of the raft. The design concept of the connected piled-raft foundations is to lessen the number of piles and utilize the bearing capacity of the system piled raft. Due to significant straining actions at the pile head-raft connection, an alternative technique is proposed to disconnect the piles from the raft. A granular layer (cushion) beneath the raft is incorporated. The disconnection has a beneficial effect on reducing axial load compared to connected piles. For small piled rafts, nonconnected piled rafts show less stiffness than connected piled rafts, and the soil is highly stressed and shows greater raft settlement. In the case of the large piled raft, nonconnected piled rafts show greater settlement efficiency. Cushion stiffness was realized to be more substantial for a nonconnected piled raft with shorter piles than one with longer piles. The results show that the load transfer mechanism in a nonconnected piled raft is mainly governed by the thickness and stiffness of the cushion layer and by the stiffness of the subsoil.